2012
DOI: 10.3857/roj.2012.30.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome in patients with vulvar cancer: comparison of concurrent radiotherapy to postoperative radiotherapy

Abstract: PurposeTo evaluate outcome and morbidity in patients with vulvar cancer treated with radiotherapy, concurrent chemoradiotherapy or postoperative radiotherapy.Materials and MethodsThe records of 24 patients treated with radiotherapy for vulvar cancer between July 1993 and September 2009 were retrospectively reviewed. All patients received once daily 1.8-4 Gy fractions external beam radiotherapy to median 51.2 Gy (range, 19.8 to 81.6 Gy) on pelvis and inguinal nodes. Seven patients were treated with primary conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…According to past domestic studies, it has been reported that radiotherapy alone could achieve excellent local control and less complications in vulvar cancer. 35 Although there were no changes in the types of surgical procedures employed during our study period, previous studies have shown changes due to the introduction of less radical surgery. 33 36 37…”
Section: Discussionmentioning
confidence: 71%
“…According to past domestic studies, it has been reported that radiotherapy alone could achieve excellent local control and less complications in vulvar cancer. 35 Although there were no changes in the types of surgical procedures employed during our study period, previous studies have shown changes due to the introduction of less radical surgery. 33 36 37…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, Han et al [ 11 ] reported 5-year rates for relapse-free survival and OS of 43% and 54%, respectively, in 14 patients who received primary chemoradiation therapy. Lee et al [ 12 ] reported 5-year DFS and OS rates of 42.2% and 46.2%, respectively, in heterogeneous patients treated with primary or adjuvant RT with or without concomitant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A high mortality rate (up to 20%) has been reported in cases of advanced-stage disease following surgical procedures [ 10 ]. The survival outcomes after definitive RT with chemotherapy vary from 46.2% to 65.0% [ 11 12 13 ]. Although the probability of tumor control by RT in patients with small tumors is similar to that for surgery, the results have generally been poor in terms of both the local control rate and the treatment-related toxicity in patients with stages III-IV vulvar cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single-agent chemotherapy has an ORR of about 12% [ 5 ]. Patients with primary disease who are not candidates for upfront surgery have a reported response rates from 55% [ 30 ] to 64% [ 11 ]. Only patients who undergo treatment on protocol will be eligible for analysis.…”
Section: Methodsmentioning
confidence: 99%